(untitled) (Italian Journal of Public Health, 2006)
The aim of the present paper is to analyse the mortality from external causes in the Umbria region, from 1994 to 2004, in order to have an indication of the effectiveness of primary prevention interventions. Sex and cause-specific AADR (the age-adjusted death rates) and YPLL rates (the age-adjusted rates of years of potential life lost up to 74 yrs) time trends were analysed by means of joinpoint regression utilising SEER software. The expected annual percent change and its significance were also calculated. The cause groups examined were: all external causes, transport accidents, falls, accidental poisoning and exposure to noxious substances, intentional self-harm and assault. The age-adjusted death rates from the selected external causes showed, in both sexes, a decreasing trend. The joinpoint regression of AADR indicated that all statistically significant variations are declining. For the AADR cause group significant decreases were found in all external combined and poisoning causes for both sexes, transport accidents and falls for females. Among males the age-adjusted YPLL rates showed significant decreases for all external causes combined (EACP = -2.8%). This analysis provides a useful tool to evaluate the effectiveness of interventions performed in the last decade and indicates that further assessment and monitoring are needed.